Three new species of Atalophlebiinae (Ephemeroptera: Leptophlebiidae) of India, with a new record of the genus Megaglena Peters and Edmunds, 1970 - Vasanth, M.; Subramanian, K. A.; Selvakumar, C.; Kubendran, T.; Sivaramakrishnan, K. G. (Zootaxa, 2021)
Three new species of Leptophlebiidae viz., Choroterpes (Choroterpes) andamanensis Vasanth, Subramanian & Selvakumar n. sp., Edmundsula meghamalaiensis Vasanth, Subramanian & Selvakumar n. sp. and Megaglena agasthiya Vasanth, Subramanian & Selvakumar n. sp. are described based on our recent exploration of mayflies from the streams of Andaman Island, Tamil Nadu and Kerala part of the southern Western Ghats. The genus Megaglena Peters & Edmunds, 1970 has extended the distribution in southern peninsular India as represented by the occurrence of M. agasthiya n. sp. Larval key is provided to the known and new species of subgenus Choroterpes of India along with the distribution map of new species.